INTERACTIVE TECHNOLOGIES AS A MEANS OF FORMATION OF COMMON CULTURAL AND PROFESSIONAL STUDENTS’ COMPETENCIES IN PEDAGOGICAL INSTITUTES - Zhestkova, Elena; Gubanichina, Elena; Oparina, Svetlana; Sidorskaya, Viola; Gusev, Dmitriy (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article describes the interactive forms and technologies that contribute to the formation of common cultural and professional competencies in students in pedagogical high school.Interactivity - is "the ability to interact with or be in the mode of dialogue" When traditional methods of teaching dialogue is possible only as the interaction between "teacher - student" and "teacher - student group (audience)", then the interactive learning in addition to this dialogue is constructed as the interaction "disciple - disciple" (work in pairs), "student - student group" (group work), "student - audience" or "group of students - the audience" (presentation of group work), "student - computer", "student - a work of art.According to the authors, the implementation in practice of the Higher School of interactive teaching methods improve the efficiency of the educational process, will teach students on the basis of acquired knowledge, not only to deepen the understanding of the theory, but also to solve the problematic issues, to analyze complex teaching situations, to work together, allow to enrich their own experience , to develop the necessary common cultural and professional competence of future teachers, and most importantly - ensures successful operation and competitiveness of graduates in their chosen professional field.